Listening and Documenting in The Reggio Approach: The Challenge And The Vision Stemming From Bruner’s Contribution - Massimelli, Massimiliano; Mineo, Roberta; Tucci, Giulia (Encounters in Theory and History of Education / Rencontres en Théorie et Histoire de l'Éducation / Encuentros en Teoría e Historia de la Educación, 2022)
The pedagogy of listening was born and developed in Reggio Emilia’s schools in northern Italy. This article analyses the pedagogy of listening in the light of the fundamental texts of the Reggio Approach literature. The aim is to explore some key concepts such as language, context, relationship, and evaluation, and also to link them to Jerome Bruner’s work and contributions. Moreover, the authors attempt to offer an in-depth view of “documentation” as the crucial tool to ground listening into the dynamics among the many educational actors involved. In the last part of the article, we underline the importance of democratic values in the Reggio Approach and in its socio-constructivist approach to active citizenship and children’s rights.